Names in Aramaic Texts of the Old Testament - Saleh, Rania; Monshid , Moayad (Al-Adab Journal, 2025)
Writing about proper names in any society goes beyond being merely personal labels; They reflect cultural and historical folds that reveal multiple aspects of the societies to which they belong.This study aimed to: define the Aramaic language, including its origins, historical development, and what is related to it and its influence on the Hebrew language; Definition of the term proper name historically and linguistically; Classifying the types of proper nouns and understanding everything related to them in terms of formation and meaning; Analysis of compound personal proper names and how they are formed and used in Aramaic texts. The study used the comparative historical analytical method. The study concluded: The imperial languages ​​(Akkadian and Persian) had the most influence on Aramaic, and their words were more permeated in Aramaic. The Aramaic language at no time was able to significantly influence Hebrew; That there is a great similarity in the phonetic roots of names between ancient Aramaic and Syriac, with slight differences in phonetic formation; Many flags came that only carry their lexical meaning to which they refer to a language. Some names show slight changes in pronunciation, such as changing the sounds of the letters or inserting additional letters, such as: “Artaxerxes” in Syriac and “אַרְתַּחְשַׁשְתָּא” in Aramaic. They show a difference in phonetic formation despite the great similarity; the most common compound proper names appear in the Books of Daniel and Ezra. They are (Daniel) and (Nebuchadnezzar), and they are mentioned (15) times. They are followed by the name (Abdnau), which is mentioned (14) times, while the least frequent are (Ashurbanipal), which is mentioned once, then (Jehoiakim) and (Shealtiel). Which was mentioned twice: that there is a clear correspondence in the sounds between Aramaic and Syriac for some names, such as the repetition of the sounds B- L- SH- TZ- N- Y- D- A- G in both languages; Language, such as the letters (א, א) in ancient Aramaic, which correspond to the letters (ܐ) in Syriac as well. Some sounds, such as “SH” in Aramaic, are written as “ܫ” in Syriac, which shows the phonetic diversity between the two languages. The study recommends research in the rest of the proper names in Old Testament Aramaic, especially single proper names, and the names of peoples and geographic locations.